2006
DOI: 10.1196/annals.1373.007
|View full text |Cite
|
Sign up to set email alerts
|

Status of Mastitis as an Emerging Disease in Improved and Periurban Dairy Farms in India

Abstract: While reviewing present status of mastitis in India, results of investigations from periurban dairy farms on epidemiological, clinical manifestations, diagnosis, bacterial isolation, in vitro drug sensitivity, and treatment of subclinical mastitis have been presented. Mastitis, on account of its causing serious wastage and undesirable milk quality, is emerging as a major challenge among the others (like breeding improvement, nutrition management, control of infectious, tick-borne, blood, and internal parasitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 2 publications
4
57
2
1
Order By: Relevance
“…Joshi and Shrestha [24] reported that 75.9% of the cases were during summer and only 5.4% in winter in Murrah buffaloes. Joshi and Gokhale [26] observed subclinical mastitis incidences were more in monsoon season compared to winter. However, Shathele [27] reported that incidence of mastitis was higher in colder months in Holstein-Friesian and showed significant effect of season on incidence of mastitis on new cases.…”
Section: Discussionmentioning
confidence: 99%
“…Joshi and Shrestha [24] reported that 75.9% of the cases were during summer and only 5.4% in winter in Murrah buffaloes. Joshi and Gokhale [26] observed subclinical mastitis incidences were more in monsoon season compared to winter. However, Shathele [27] reported that incidence of mastitis was higher in colder months in Holstein-Friesian and showed significant effect of season on incidence of mastitis on new cases.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the SCM was increasing and CM prevalence was decreasing over the past six year period . Further, there was high heterogeneity was observed between various studies for the estimates of mastitis prevalence and it might be due to various factors like parity of cattle, lactation stage and genetic makeup of animals, agroclimatic conditions and farm managemental practices (Joshi and Gokhale, 2006). More number of studies on SCM (32) and CM (19) prevalence are being reported during 2011-16 indicating the importance of mastitis in dairy cows in India during recent years.…”
Section: Meta-analysis Of Subclinical and Clinical Mastitismentioning
confidence: 99%
“…India being one of the largest producers of milk is at risk with respect to bovine mastitis and in particular, subclinical mastitis is found to be more important varying from 10 to 50 % in cows and 5 to 20 % in buffaloes than clinical [16]. During such subclinical forms, the latent inflammatory reaction within the mammary gland is detectable only through the culturing of milk for the identification of the residing pathogen [17].…”
Section: Discussionmentioning
confidence: 99%